Evaluation of a range of mammalian and mosquito cell lines for use in Chikungunya virus research. Issue 1 (December 2017) - Roberts, Grace; Zothner, Carsten; Remenyi, Roland; Merits, Andres; Stonehouse, Nicola; Harris, Mark
Abstract Chikungunya virus (CHIKV) is becoming an increasing global health issue which has spread across the globe and as far north as southern Europe. There is currently no vaccine or anti-viral treatment available. Although there has been a recent increase in CHIKV research, many of thesein vitro studies have used a wide range of cell lines which are not physiologically relevant to CHIKV infectionin vivo . In this study, we aimed to evaluate a panel of cell lines to identify a subset that would be both representative of the infectious cycle of CHIKVin vivo, and amenable toin vitro applications such as transfection, luciferase assays, immunofluorescence, western blotting and virus infection. Based on these parameters we selected four mammalian and two mosquito cell lines, and further characterised these as potential tools in CHIKV research.